2022
DOI: 10.3390/cancers14246219
|View full text |Cite
|
Sign up to set email alerts
|

The Lymphatic System, Lymphoedema, and Medical Curricula–Survey of Australian Medical Graduates

Abstract: The aim of this study was to survey the perceptions of recent (i.e., within the past 12 months) Australian medical graduates regarding (i) their understanding of the lymphatic system and lymphoedema, and (ii) the extent to which the lymphatic system and lymphoedema were covered as part of their medical degree. Medical graduates were invited to participate in a 17-item online survey that asked respondents to rate their level of agreement (using a 5-point Likert scale; higher scores = higher agreement) to statem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Making the right diagnosis is related to the knowledge of healthcare providers and there is a substantial gap in this field [33,34]. Lymphedema is somehow neglected in medical research and education and the outcome of this neglect would reflect on clinical practice [35][36][37] Šimek et al reported similar results in their prospective trial comparing minimally invasive and endoscopic great saphenous harvesting. Lymphatic discharge was significantly lower among the endoscopic group at seven days post-operation.…”
Section: From Neglecting Lymphedema To the Patient's Qolmentioning
confidence: 97%
“…Making the right diagnosis is related to the knowledge of healthcare providers and there is a substantial gap in this field [33,34]. Lymphedema is somehow neglected in medical research and education and the outcome of this neglect would reflect on clinical practice [35][36][37] Šimek et al reported similar results in their prospective trial comparing minimally invasive and endoscopic great saphenous harvesting. Lymphatic discharge was significantly lower among the endoscopic group at seven days post-operation.…”
Section: From Neglecting Lymphedema To the Patient's Qolmentioning
confidence: 97%